PERLINDUNGAN HUKUM TERHADAP PENCIPTA ATAS BUKU BAJAKAN YANG DIPERJUALBELIKAN MELALUI E-COMMERCE - Faradila Khairunisa (JOURNAL OF LAW AND NATION, 2024)
Legal protection for book copyright has been regulated in the Copyright Law, namely Law Number 28 of 2014 concerning Copyright. This legal protection aims to protect the rights of creators. However, even though there are regulations related to copyright, copyright violations still continue to occur, such as piracy of books as copyrighted works and then buying and selling them through e-commerce platforms. For this reason, what is the legal protection for copyright for pirated books that are bought and sold via e-commerce? The method that will be used in this research is normative, because it carries out a study and evaluation of applicable laws and regulations. Based on the results of the discussion, it was found that with legal protection for copyright, it is hoped that copyright violations will decrease and creators can feel that their work or creations are respected and protected by the state.